2015
DOI: 10.1177/0142723715596647
|View full text |Cite
|
Sign up to set email alerts
|

Communicative intentions of child-directed speech in three different learning environments: Observations from the Netherlands, and rural and urban Mozambique

Abstract: This article compares the communicative intentions observed in the speech addressed to children of 1;1 and 1;6 years old from three cultural communities: the Netherlands, rural Mozambique, and urban Mozambique. These communities represent two prototypical learning environments and a third hybrid: Western, urban, middle-class families; non-Western, rural, subsistence-farming families; and non-Western, urban learning environment. The results show that the Dutch CDS contains relatively more utterances with a cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 31 publications
4
47
2
5
Order By: Relevance
“…Inspection of multiple age groups in the Tsimane data revealed that estimates of directed, one-on-one speech quantity were remarkably similar for interactants between birth and 4 years of age, and that the amount of time speaking to children was similar to that spent talking to others only when analyzing much older children, aged between 8 and 11 years, as interactants. These results seem to suggest differences when compared to previous work in preindustrial societies mentioned in the Introduction, which has documented increases in input quantity when comparing 17-or 30-month-old infants against 13-or 14-month-olds (Shneidman, 2010;Vogt et al, 2015).…”
Section: Integrating Present Work With Previous Researchcontrasting
confidence: 82%
See 3 more Smart Citations
“…Inspection of multiple age groups in the Tsimane data revealed that estimates of directed, one-on-one speech quantity were remarkably similar for interactants between birth and 4 years of age, and that the amount of time speaking to children was similar to that spent talking to others only when analyzing much older children, aged between 8 and 11 years, as interactants. These results seem to suggest differences when compared to previous work in preindustrial societies mentioned in the Introduction, which has documented increases in input quantity when comparing 17-or 30-month-old infants against 13-or 14-month-olds (Shneidman, 2010;Vogt et al, 2015).…”
Section: Integrating Present Work With Previous Researchcontrasting
confidence: 82%
“…So does presence of siblings, in particular, and others, in general, increase or decrease the quantity of speech addressed to young children when all cultures are taken into account? Although different researchers have studied different parameters (Vogt et al., provide number of people living in the household, Shneidman & Goldin‐Meadow, the number of people present in the video recordings, and we report number of people in the same location), inspection of previously published results appears to support the idea that more people leads to less directed one‐on‐one speech: Children in the Mayan and Mozambique settings have averages of 7–8 people (in the video recording and household, respectively) and received between 40 and 240 directed utterances per hour, whereas American and Dutch children, with about three people in their environment, heard 400–650 sentences. This factor, however, does not account for variance in our data, as similar group sizes are found surrounding children of different ages (averaging 5.9–7.7), who differ greatly in terms of frequency of directed speech.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…This paper presents a novel adaptation of the CDI short version [9] into three languages spoken in Mozambique: Changana, Ronga, and (Mozambican) Portuguese. The adaptation was designed for the purpose of a study on the cultural and social aspects of language acquisition in a rural monolingual Changana speaking community and an urban, bilingual Ronga and Portuguese speaking community [10][11][12]. Changana and Ronga are mutually intelligible Southern Bantu languages within the Tsonga language group, which is also spoken in parts of South Africa [13,14].…”
Section: Introductionmentioning
confidence: 99%